Solve for n -11n-18=-2n+9

Math
-11n-18=-2n+9
Move all terms containing n to the left side of the equation.
Tap for more steps…
Add 2n to both sides of the equation.
-11n-18+2n=9
Add -11n and 2n.
-9n-18=9
-9n-18=9
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 18 to both sides of the equation.
-9n=9+18
Add 9 and 18.
-9n=27
-9n=27
Divide each term by -9 and simplify.
Tap for more steps…
Divide each term in -9n=27 by -9.
-9n-9=27-9
Cancel the common factor of -9.
Tap for more steps…
Cancel the common factor.
-9n-9=27-9
Divide n by 1.
n=27-9
n=27-9
Divide 27 by -9.
n=-3
n=-3
Solve for n -11n-18=-2n+9

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top